Educação estética e razão comunicativa: um outro da razão ou uma outra racionalidade? - Azevedo, Mauricio Cristiano de (2007)
Bibliographic and filmic analysis towards an exercise on a reconstructive hermeneutics reading of Schiller s Letters for an Aesthetic Education of Human Being connected to the communicative rationality in Habermas. This conection is processed dua to Habermas dedication of a passage on this Philosophical Discourse of Modernity to the analysis of Schiller s Letters. The prevalently analysed phenomena, besides contemplating an explanation on the Bildung, are focused also on the view of the relations of proximity between aesthetic rationality and ethical rationality. In this sense, we seek to retrieve aesthetics and art from the confinements of being traditionally considered a territory belonging to the other of reason of theory, going on to compose along with the sensitive elements and with ethicity, and another theoretical horizon . Thus, the way towards comprehensing the other involves, more then an opening within traditional rationality, an opening towards another rationality. And this not only so that the comprehension of tradition is maintained, but also for the awareness of problems in which tradition wasn t able to advance. This other rationality we here seek to approach is the aesthetical issue in its articulattive nexus with the ethical problem, in an approach that gains force within the contemporary philosophical environment. Fort such purpose we use an empirical support in the form of the movie Dead Poet Society, interpreting it as an education metaphor where the problems of traditional strictness are contrasted with the changes brought on by the approximation to the elements of aesthetic experience. Concluding, we bring forward, intending on opening a debate, the issue of the formative force of our time.